Relationship between fear memory and gut microbiota colonization (Research, Society and Development, 2025)
This study investigated the relationship between exposure to Mozart’s Sonata K448 and the gut microbiota of aging mice, focusing on memory. Music has been used therapeutically to promote cognitive improvements, and the gut microbiota plays a key role in the communication between the nervous system and the gut, influencing cognitive disorders. The aim was to analyze the effects of exposure to Mozart’s Sonata K448 on the gut microbiota of mice. The mice were divided into three groups: G1 (Mozart), G2 (Environment), and G3 (Control). Group G1 was exposed to the music from the fetal stage for 10 hours until the fecal collection. The fecal samples were processed in selective (MacConkey) and non-selective (Nutrient) media, and bacterial colonies were counted. Before the memory test, the control group showed no bacterial growth, while the Mozart group showed a significant increase compared to the Environment group. After the memory test, the control and Mozart groups showed an increase in colony count, while the Environment group showed a sharp decrease. No growth of enterobacteria was observed in the control group, and both the Mozart and Environment groups showed a reduction in colony number after the memory test. These results indicate that exposure to Mozart’s Sonata K448 has a significant impact on the bacterial colony count and diversity in the feces of mice, suggesting an interaction between music and the gut microbiota that may influence cognitive functions.